(untitled) (PANGEEA, 2025)
The harmful consequences of radical transformations in the economic, political, ideological, axiological spheres, combined and amplified by the information explosion, the media promotion of subcultural products, the weakening of social control and the power of intervention of the instances of socialization of the younger generation, all this has damaged the social equilibrium, produced a deep moral and axiological crisis, led to an erosion of the moral-relational community, and increased the number of individuals and groups abusing constitutional freedoms and systematically leading a way of life incompatible with social norms. The latter are also undergoing changes dictated by the transition to a market economy, which is creating psychological discomfort for social actors and affecting and, above all, confusing the younger generation. Lacking real life experience and a critical view of the false information with which they are bombarded, this generation is incapable of properly evaluating social events and phenomena. Thus, lacking a well-developed axiological and self-regulatory system, it adopts patterns of behavior that are socially undesirable, indicative of poor social adaptation. In general, nothing can justify a rapprochement, other than paradoxically, between violence and the creativity of its discovery. Violence implies impulsiveness, unrestraint, brutality, force and power. Violence is the opposite of emotional harmony.